Técnicas didácticas aplicadas a la formación del contador público - Ramírez Tapias, Diego; Chamorro González, Candy; Rodelo Sehuanes, Mario; Vásquez Montoya, Olga; Velásquez Pérez, Mariela; Bustos Sierra, Sergio; Garavito Robayo, Gabriel (Universidad Católica Luis Amigó, 2023)
This book presents theoretical approaches and work experiences of the professors in the Public Accounting program at Universidad Católica Luis Amigó regarding the projected and applied didactic techniques in their art of teaching accounting. The first section provides a brief contextual introduction to didactics based on its historical background. Next, the strategies and didactic techniques used in the teaching and learning process of accounting professionals are determined. The third section reveals the didactic techniques used for accounting education, and finally, chapter four delves into other didactic techniques derived from pedagogical fieldwork. In this way, this academic text intends to generate debate among the accounting community.